A historical study of appendicular fractures in veterans with traumatic chronic spinal cord injury: 2002–2007. (1st November 2016) - Bethel, Monique; Bailey, Lauren; Weaver, Frances; Harmon, Robert L.; Priebe, Michael M.; Le, Brian; Aslam, Hammad; Fausel, Zachary; Hoenig, Helen; Carbone, Laura D.
Abstract : Objective : Describe the incidence and distribution of appendicular fractures in a cohort of veterans with spinal cord injury (SCI). Design : Retrospective, observational study of fractures in veterans with a chronic traumatic SCI. Setting : The Veterans Health Administration (VA) healthcare system. Participants : Veterans included in the VA Spinal Cord Dysfunction Registry from Fiscal Years (FY) FY2002–FY2007. Interventions : Not applicable. Main Outcome Measures : Description of fractures by site and number. Mortality at one year following incident fracture among men with single vs. multiple fractures. Results : Male and female veterans sustained incident fractures with similar observed frequency (10.5% vs 11.5%). The majority of fractures occurred in the lower extremities for both men and women. In men, a complete extent of injury (compared to incomplete) was associated with 41% greater relative risk (RR) of incident fracture (RR 1.41, 95% confidence interval [1.17, 1.70]) among those with tetraplegia, but not paraplegia. Furthermore, many men (33.9%, n = 434) sustained multiple fractures over the course of the study. There were no differences in mortality between men who sustained a single fracture and those who had multiple fractures. Conclusions : The extent of injury may be an important predictor of fracture risk for male veterans with tetraplegia. Once a fracture occurs, male veterans with SCI appear to be at high risk for additional fractures.